2018
DOI: 10.1080/19420862.2018.1522178
|View full text |Cite
|
Sign up to set email alerts
|

Antigen binding allosterically promotes Fc receptor recognition

Abstract: A key question in immunology is whether antigen recognition and Fc receptor (FcR) binding are allosterically linked. This question is also relevant for therapeutic antibody design. Antibody Fab and Fc domains are connected by flexible unstructured hinge region. Fc chains have conserved glycosylation sites at Asn297, with each conjugated to a core heptasaccharide and forming biantennary Fc glycan. The glycans modulate the Fc conformations and functions. It is well known that the antibody Fab and Fc domains and … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
59
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(68 citation statements)
references
References 103 publications
(117 reference statements)
6
59
0
Order By: Relevance
“…Because we previously demonstrated allosteric communications between the V-and C-regions on IgAs 30 and such an effect was also reported on IgGs by many other research groups, [26][27][28][29] we next sought to study whether such allosteric effects explained the differences in FcεRIa binding present in our pertuzumab IgE variants. To do this, we computationally modeled the full-length structures of all the pertuzumab IgE variants and quantified the allosteric communications between the V-and C-regions by using the AlloSigMA server (Fig 3, B).…”
Section: Effect Of Vh Fwrs On Fcεria Bindingmentioning
confidence: 71%
See 1 more Smart Citation
“…Because we previously demonstrated allosteric communications between the V-and C-regions on IgAs 30 and such an effect was also reported on IgGs by many other research groups, [26][27][28][29] we next sought to study whether such allosteric effects explained the differences in FcεRIa binding present in our pertuzumab IgE variants. To do this, we computationally modeled the full-length structures of all the pertuzumab IgE variants and quantified the allosteric communications between the V-and C-regions by using the AlloSigMA server (Fig 3, B).…”
Section: Effect Of Vh Fwrs On Fcεria Bindingmentioning
confidence: 71%
“…20 They are reported to interact with specific VH FWRs (eg, protein A [spA] to some VH3 FWRs), [21][22][23][24] but because not all the same VH FWRs bind to such superantigens, there is no reason to believe that VH FWRs are the sole factors in superantigen binding. As a possible mechanism for superantigen activation of FcεRIa-bound IgE, recent investigations on antibodies have demonstrated that antigen binding at antibody V-regions can elicit structural changes that facilitate cell signaling 25 and that even VH families can elicit distal effects on antibody constant regions (C-regions) for IgGs [26][27][28][29] and IgA. 30 This allosteric effect was also shown when the changing of antibody C-regions affected antigen binding.…”
mentioning
confidence: 99%
“…We outline several tactics to modulate Fc activity linked to FcγR for immune effector cell function and FcRn for pharmacokinetic properties. Nonetheless, it is critical to keep in mind that the Fab domain antigen binding can affect the Fc region activity via structural allostery [398][399][400]. Hence, evaluations of specific Fc mutations should be confirmed empirically.…”
Section: Fc Activity Engineeringmentioning
confidence: 99%
“…Furthermore, crystal structures of intact IgGs also indicate that the hinge-regions are largely responsible for this flexibility, although these regions tend to be poorly resolved and in the confines of a crystal lattice (68). However, detailed dynamics studies of antibody behavior in solution provide computational evidence that antigen binding changes the sampling space of Fc as well as the flexibility, providing a type of "rigidity" that is not found in unbound antibodies, which may lead to greater FcγR affinity in the presence of antigen (254).…”
Section: Antibody Allosterymentioning
confidence: 99%